2017
DOI: 10.5194/isprs-annals-iv-2-w2-271-2017
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Preservation of the Physical Remains of the Destroyed Buddha Figures in Bamiyan (Afghanistan) Using Virtual Reality Technologies for Preparation and Evaluation of Restoration Measures

Abstract: ABSTRACT:In March 2001, the world's largest depictions of standing Buddha figures located in Bamiyan (Afghanistan) were destroyed during a campaign of the Taliban leadership against all non-Muslim heritage in the country. Bamiyan and its archaeological remains have been nominated a World Heritage also to commemorate the events of destruction the site has experienced over the centuries. More than fifteen years after the Giant Buddha figures turned into dust, the UNESCO Safeguarding campaign for the preservation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…4), a 3D digital model of the 38 m Buddha could be generated (Toubekis et al 2011) and serves as basis for the surface calculation. (Toubekis et al 2017). The values for the total volume stay in the same range (~11%), much less of the assumed remains of 40-45% that was claimed so far (ICOMOS, 2016, p. 239).…”
Section: Assessment Of the State Of Conservation Of The Eastern Buddhmentioning
confidence: 54%
“…4), a 3D digital model of the 38 m Buddha could be generated (Toubekis et al 2011) and serves as basis for the surface calculation. (Toubekis et al 2017). The values for the total volume stay in the same range (~11%), much less of the assumed remains of 40-45% that was claimed so far (ICOMOS, 2016, p. 239).…”
Section: Assessment Of the State Of Conservation Of The Eastern Buddhmentioning
confidence: 54%
“…Many criteria were used (i, ii, iii, iv and vi), describing the relevance of Gandaharan art in this region, the interchange of diverse religious and cultural traditions, the cultural tradition, the cultural landscape but also the direct and tangible association with a tragic, violent and deliberate destruction of irreplaceable cultural heritage in the twenty-first century A.D. As a consequence, the destruction is part of the OUV, and any physical revitalisation has to bear this in mind. This point was well established since 2003, during the nomination process, since it was very clear that most of original rock was pulverised (89% according to Toubekis et al 2017), due to its low consistency, the vertical variability of rock mechanical parameters and the energy of blasting in a close environment that the niche is. Visibly, a large percentage of such remaining fragments comes from the interior of the statue, and, unfortunately, there is no record of the exterior surface of the statue.…”
Section: An Appropriate Conservation Philosophy Based On the Outstandmentioning
confidence: 95%
“…After the destruction of giant Buddha statues, the scientific community started to investigate how to give back, to Afghanistan and to the Azar local community, a masterpiece of their history and tradition, clearly being aware that only 12% of original surface can be recovered and only 11% of original volume was not decomposed into debris and dust (Toubekis et al 2017).…”
Section: Foreword: Cutting the Root Of Culturementioning
confidence: 99%
“…• Toubekis et al (2017), that showed the use of 3D digital modelling on partially destroyed Buddha figures in Bamiyan, through superposition on a detailed 3D laser recording, and set up an immersive VR experience aimed to become the basis for scientific re-assembly of the original fragments;…”
Section: Related Workmentioning
confidence: 99%